Inclusive Practices in Physical Education: Considerations for Students With Dyslexia. Issue 6 (24th July 2022) - Pavlovic, Marko; Simonton, Kelly L.; Casey, Laura
Abstract: Not enough information on instructional practices specific for students with dyslexia in PE has been published. Given dyslexia's prevalence in the population, and the impact it has on students holistic learning, there is a tremendous need for teacher training about "best practices" when teaching those with dyslexia in all subjects, including PE. Therefore, this article will explain the key concepts of dyslexia, the multisensory approach as remedial training, and provide modification strategies that can increase student awareness, confidence, and strengths via PE learning opportunities.